Distribution, sources identification, and ecological risk of PAHs and PCBs in coastal surface sediments from the northern Persian Gulf - Nozar, Seyedeh Laili Mohebbi; Ismail, Wan Ruslan; Zakaria, Mohamad Pauzi (Taylor & Francis, 2014)
Hormozgan Province plays a vital role in fishery, petroleum, and industrial activities in southern Iran. However, no comprehensive studies on organic pollution have been performed. PCBs and PAHs were analyzed in surface sediments from areas receiving industrial (nine sites), river (one site), and urban (two sites) effluents. The sediment samples were collected in March and September 2010 (in dry and wet seasons) at the highest tidal time. The overall pollution level of PCBs ranged from 2.5 ± 0.8 to 462.0 ± 206.7 ng/g dry weight. CB153 congener dominated in most of the sediment samples. Congener profiles of PCBs showed close similarity with formulations of commercial products such as Aroclor 1260 and 1254 g. A wide range of 55.3 to 1231.6 ng/g dry weight was detected for ∑PAHs. Results of PCA and PCA-MLR tests confirmed both petrogenic and pyrogenic origins for PAH pollution. The higher means of ∑PAHs and ∑PCBs in industrial and urban wastewaters were found near the shore, evidencing the role of these wastewaters in the PAH and PCB contamination in Hormozgan sediment. The concentrations of PAHs and PCBs in detected hotspots exceed the U.S. NOAA sediment quality guidelines.